Investigating Instructional Leadership, Transformational Leadership, Self-Efficacy and Trust among Primary School Teacher - Jumadi Musa; Mohamad Nizam Nazarudin; Zakiah Binti Noordin; Nur Afny Juati; Hujaimah @ Siti Syafiqah Bt Juhumin (GLOBAL ACADEMIC EXCELLENCE (M) SDN BHD, 2020)
The purpose of this study is to investigate the relationship between headmaster instructional leadership, headmaster transformational leadership, self-efficacy, and trust among primary school teachers. Furthermore, the study aims to examine the role of gender, age, and teaching experience in headmaster instructional leadership, headmaster transformational leadership, and self-efficacy. The participants were selected by proportional stratified sampling and simple random selection. This study adopted a survey research design that utilized an ex-post facto research type in which the researcher used questionnaires to collect data from the respondents. The instruments used are the Principal Instructional Management Rating Scale (PIMRS), Multi-factor Leadership Questionnaire (MLQ), Teachers' Sense of Efficacy Scale (TSES), and Trust Scale - Trust in Principal. A total of 297 respondents (mean age 37.4 + 1.5 years) from 71 schools were involved in this study. The data gathered from the respondents were downloaded into the Statistical Package for the Social Sciences (SPSS) for quantitative analysis. The results of the study indicate that there is a positive significant relationship between headmaster instructional leadership (r = .708, p <.05), headmaster transformational leadership (r= .683, p<.05), self-efficacy (r = .615, p <.05) and trust. It is found there is no significant difference among primary school teachers of different ages and teaching experience concerning their headmaster instructional leadership [F (2, 296) = 1.533, p> 0.05][F (2, 296) =. 878, p> 0.05], , headmaster transformational leadership [F(2, 296)=.396, p> 0.05][F(2, 296)=.396, p> 0.05] and teacher efficacy [F (2, 296) = 1.164, p> 0.05] [F (2, 296) = 1.204, p> 0.05]. The present study gains significance as the results can assist the teachers and organizations in enhancing the thrust of teachers.